Genera of eulophidae (HYMENOPTERA: CHALCIDOIDEA) present in orange orchard in the state of Morelos, Mexico - Fuentes Guardiola, Lucía Teresa; García Martínez, Oswaldo; Sánchez Peña, Sergio René; Corrales Reynaga, Jorge (Instituto de Ecología, A.C., 2017)
Due to the economic importance of citrus in the world and the use of Eulophidae species in biological control programs, biweekly collects of entomological material were performed for 12 months in a citrus orchard of the state of Morelos, Mexico. A total of 23 genera of Eulophidae were determined in the four subfamilies that integrate this family, ten of Tetrastichinae, nine of Eulophinae, three of Entedoninae and one of Entiinae.